Kenaf (Hibiscus cannabinus L.) as a remedy to oxisol contaminated with different mercury (Hg2+) concentrations - Lavezzo, Letícia Fernanda [UNESP]; Delarica, Denise De Lima Dias [UNESP]; Fostier, Anne Hélène; Rigobelo, Everlon Cid [UNESP]; Santos, Roberta Mendes Dos [UNESP]; de Almeida, Camila Chioda; Souza, Danilo Olandino [UNESP]; de Melo, Wanderley José [UNESP] (Southern Cross Publishing, 2021)
We evaluated Hibiscus cannabinus (kenaf) to remedy oxisol contaminated with Hg2 + potential. The study was conducted in a controlled environment in pots with soil contaminated with HgCl2 solution, in a completely randomized design with 4 treatments: control (without Hg2+) and treatments with 5, 24 and 36 mg Hg2+ kg-1 of soil and 5 replicates / treatment. The quantification of total Hg in plant and soil samples was performed by atomic absorption spectrometry. Kenaf grown in contaminated pots did not show visual symptoms of toxicity. Plant height did not differ among treatments, but the dry shoot phytomass was 21.65% higher in control than the average of treatments with Hg. Treatment with 24 mg kg-1 showed dry root phytomass greater than control and the others. In general, oxisol was responsible for retaining greater amount of Hg than plants. Hg accumulated in greater proportion in roots than in shoots. In pots that received 36 mg kg-1, plants accumulated average of 2.57 mg kg-1 of Hg / pot, differing from the other treatments and the Hg transfer factor (TF) in plants was also calculated as the ratio of the concentration in shoots and in roots. The values were as follows: 3.11 for T1, 1.26 for T2, 0.05 for T3 and 0.02 for T4. Treatments showed no difference between T3 and T4 and TF decreased with increasing Hg dose. It could be concluded that Hg was more adsorbed by oxisol than by plants. Plants showed resistance to different soil Hg concentrations and can be considered as potential Hg2+ stabilizer.
Keywords: contamination; soil remediation; toxic metal